A web-based ergonomics assessment system for prioritizing critical work-related musculoskeletal disorders risk factor - Fazilah, Abdul Aziz; Z., Ghazalli; N. M. Zuki, N. M. (IOP Publishing, 2020)
Work-related musculoskeletal disorder (WMSD) is one of critical health disease, and large numbers of industry workers are not even aware they have it due to a lack of ergonomics knowledge. This paper seeks to describe the development of a web-based ergonomics assessment system (W-BEAS) for risk factors that lead to WMSD growth. There are four main ergonomics risk factors, and 26 sub-factors have selected based on literature review, discussions with experts and questionnaire survey among automotive production workers. These factors employed in the analytic hierarchy structure (AHP) model for analysis purpose. The integration of AHP and the web-based expert system (WBES) were developed to support the W-BEAS. W-BEAS had pre-tested and evaluated by ten experienced workers of an automotive component manufacturer. The inconsistency ratio for all comparison module ranged from 0 to 0.045, shows that the judgment is consistent because of value less than 0.1. Respondents considered organizational risk factor (OF=0.544) is the most critical to lead the WMSD growth. The respondents achieve an average of 3.95 for both content satisfaction and system satisfaction. Respondents were satisfied with WBEAS content and system performance. The preliminary results confirmed that the W-BEAS effectively helped workers to identify the critical ergonomics risk factors. The existence of the W-BEAS application that has designed is expected to be an ergonomics assessment tool to guide workers in decision-making, and provide the best solution that meets employer needs, so WMSD critical risk resolved effectively and efficiently.